Applying Sen's Capabilities Approach to the Delivery of Positive Youth Justice. (April 2021) - Williams, Katherine S.; Daniel, Heddwen
Since 2000 the Welsh Government's (WG) policy has been to provide rights and entitlements to all children in Wales. However, this is not fully implemented partly due to an underspecified meaning of 'children first' and 'well-being' and their role in relation to 'justice'. We propose that clarity could be achieved through a novel exploitation of Amartya Sen's capabilities approach to achieving social justice. This would require the identification and mitigation of socio-structural barriers which undermine the ability of a child to live a positive life, a life where they can meet their full potential without harm to themselves or others.